The unequal inequality impact of the COVID-19 pandemic - Zsolt M. Darvas (Bruegel, 2021)
GDP contractions are typically associated with within-country income inequality increases. While official income inequality data for 2020 will not be available for about two years, the already available employment data for 2020 shows that the difference between highly-educated and low-educated people in terms of job losses is correlated with the economic shock from the COVID-19 pandemic, suggesting that the depth of the economic recession is related to the increase in within-country income inequality in 2020. Scenarios based on historical patterns of recessions and within-country income inequality increases suggest relatively small increases in global income inequality in 2020. Factors mitigating global inequality increases in 2020 include larger GDP per-capita declines in richer advanced countries than in poorer emerging and developing countries, and the positive GDP growth of China, which suggests that within-country inequality in the world's most populous country might have not changed much in 2020. In contrast, it is quite likely there was a signifi cant increase in European Union income inequality in 2020, partly reversing the decline during the previous decades.
Keywords: C63; D31; D63; O15; 330; COVID-19; employment; global distribution of income; income inequality